IMPLEMENTASI PEMBELAJARAN PENDIDIKAN PANCASILA BERMUATAN ISLAM TERPADU UNTUK MENGUATKAN KARAKTER LEADERSHIP PADA SISWA KELAS VII SMPIT INSAN MULIA SURAKARTA - Laila Rachmawati; Sutoyo Sutoyo; Anita Trisiana (STKIP Pesisir Selatan, 2026)
This study aims to: (1) Identification the implementation of integrated Islamic Pancasila Education learning in strengthening the leadership character of class VII students at SMPIT Insan Mulia Surakarta, (2) Describe the obstacles in implementing integrated Islamic Pancasila Education learning in strengthening the leadership character of class VII students at SMPIT Insan Mulia Surakarta. Research informants include the principal, class VII Pancasila Education teachers, and class VII students. Data were collected through interviews, observations, and documentation, with validity tests using triangulation of sources, techniques, and time. Data analysis was carried out interactively through the stages of data collection, data reduction, data presentation, and drawing conclusions. The results of the study show that (1) Integrated Islamic Pancasila Education learning in class VII was implemented using interactive methods such as Team Games Tournament (TGT) and group debates as well as integrating Islamic values through linking material with verses of the Qur'an, so that it was able to gradually grow students' leadership character through instilling the values of responsibility, trustworthiness, and exemplary behavior. (2) The obstacle lies in the differences in student character, especially students with introverted personalities who tend to be passive and less courageous in expressing their opinions, so that strengthening of leadership character has not developed evenly even though learning has been carried out well.